The development of an analog meat product using Philippine-sourced Elkhorn Seamoss (Kappaphycus alvarezii) protein concentrate - Yabut, Cecilia Louise P.; Tolentino, Mark Paulo S., MSc (Quezon City University of the Philippines Diliman, 2023)
In response to the rising global demand for protein, emerging plant-based meat analogs have served as a sustainable meat alternative with similar nutritional and health benefits and meat consumption satisfaction. In order to improve sensory properties, enhance the worth of locally cultivated Kappaphvcus alvarezii, and diversify the range of protein sources for plant-based meat products, a seaweed protein concentrate derived from K. alvarezii was utilized in this study as a functional additive. Protein from dried seaweed was extracted and developed into patties with lupine protein to develop a similar and acceptable formulation for plant-based meat analogs relative to commercially available products. Fifty-one participants evaluated four samples, particularly the samples of plant-based meat analogs with 0%, 2%, and 5% seaweed protein and a commercial product as control. The acceptability of each sample was assessed using a 9-point hedonic scale. Results showed that there was a significant positive correlation between the acceptability of different quality attributes and the overall acceptability of the samples. The sample with 2% seaweed protein was the most preferred, followed by the sample with 5% then 0% seaweed protein, and overall, more significantly acceptable than the control. Specifically, flavor and mouthfeel contributed the most important factors influencing the overall quality, which could be influenced, along with the appearance, by the emulsifier properties, gel-forming abilities, and water-holding capacities of seaweed protein. This showed that a formulation using extracted K. alvarezii protein could be developed into an additive for an acceptable and competitive plant-based meat analog due to the enhancement in the sensory properties of the seaweed protein, despite having relatively less protein than the commercially available products. This was supported by the willingness of panelists to consume the samples with the seaweed protein. Future studies could focus on the reformulation and optimization of ingredients to further improve the sensory properties, especially the taste, aroma, and overall acceptability.
Thesis
Includes bibliographical references (pages 35-45)
Keywords: Meat substitutes -- Philippines; Marine algae as food -- Philippines; Marine algae industry -- Philippines; Red algae -- Philippines